Feasibility, efficacy and safety of tyrosine kinase inhibitor treatment in hemodialyzed patients with renal cell cancer: 10 years of experience. (August 2015) - Czarnecka, Anna M; Kawecki, Maciej; Lian, Fei; Korniluk, Jan; Szczylik, Cezary
Aims: Sine efficiency of tyrosine kinase inhibitor (TKI) therapy in dialyzed patients is still unclear we aim to analyze the outcome of treatment in such cohort.Patients & methods: We analyzed treatment outcomes of patients with clear cell renal cell carcinoma (ccRCC) with special focus on those who were also treated with hemodialysis and described treatment safety and progression-free survival of eight patients treated with TKIs and hemodialysis.Discussion & conclusion: Our report supports statement that TKI treatment of dialyzed patients is safe and effective. ccRCC increases risk of developing renal insufficiency as well as end-stage renal disease that require dialysis. Introduction of multitargeted receptor kinase inhibitors (TKIs), including sunitinib, sorafenib and pazopanib significantly expanded life time expectancy of metastatic renal clear cell carcinoma. The advance also applies to patients with ccRCC and end-stage renal disease who undergo dialyses.